2023
DOI: 10.1021/acsomega.3c01148
|View full text |Cite
|
Sign up to set email alerts
|

Influence Factors and Feasibility Evaluation on Geological Sequestration of CO2 in Coal Seams: A Review

Abstract: The geological sequestration of CO 2 in coal seams holds significant implications for coalbed methane development and greenhouse gas mitigation. This paper examines the principles, influencing factors, and evaluation methods for geological CO 2 sequestration in coal seams by analyzing relevant domestic and international findings. Suitable geological conditions for CO 2 sequestration include burial depths between 300 and 1300 m, permeability greater than 0.01 × 10 −3 μm 2 , caprock and floor strata with water i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
0
3
1
Order By: Relevance
“…An increase in the vitrinite reflectance by 0.1% resulted in a reduction of the a mCO2 value by 1.5%. The obtained observations are in contradiction to those obtained by authors dealing with the influence of coal rank on the sorption capacity [13,39], who found that as the vitrinite reflectance increased, the ability of coal to adsorb CO 2 also increased. An explanation for such observations may be the example of studies carried out in relation to CH 4 , which showed a falling and then rising trend [40].…”
Section: The Influence Of Depth On the Sorption Exchange Co 2 /Chcontrasting
confidence: 99%
See 2 more Smart Citations
“…An increase in the vitrinite reflectance by 0.1% resulted in a reduction of the a mCO2 value by 1.5%. The obtained observations are in contradiction to those obtained by authors dealing with the influence of coal rank on the sorption capacity [13,39], who found that as the vitrinite reflectance increased, the ability of coal to adsorb CO 2 also increased. An explanation for such observations may be the example of studies carried out in relation to CH 4 , which showed a falling and then rising trend [40].…”
Section: The Influence Of Depth On the Sorption Exchange Co 2 /Chcontrasting
confidence: 99%
“…Some researchers also reported that the CO 2 /CH 4 sorption ratio decreased with the coalification degree increase [13,21]. It was also shown, by examining the CO 2 /CH 4 sorption efficiency, that a higher coalification degree resulted in an increase in the CH 4 displacement rate at low pressures [22].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The burial depth and spatial form of the coal seam refer to the current occurrence state of the coal seam, which is the result of later tectonic movement after the formation of the coal seam 33 . The burial depth of a coal seam affects important reservoir parameters such as coalbed methane content, coal seam permeability, reservoir pressure and reservoir temperature.…”
Section: Results Analysismentioning
confidence: 99%
“…Monte Carlo simulation has found widespread application in estimating coalbed methane reserves. In this study, we used the Monte Carlo method to simulate values for reservoir parameters and conducted an in-depth analysis of the influence of these parameters on coalbed methane production capacity [25].…”
Section: Reservoir Parameter Uncertainty Intervalsmentioning
confidence: 99%